2021
DOI: 10.1098/rspb.2020.3052
|View full text |Cite
|
Sign up to set email alerts
|

Hard to catch: experimental evidence supports evasive mimicry

Abstract: Most research on aposematism has focused on chemically defended prey, but the signalling difficulty of capture remains poorly explored. Similar to classical Batesian and Müllerian mimicry related to distastefulness, such ‘evasive aposematism' may also lead to convergence in warning colours, known as evasive mimicry. A prime candidate group for evasive mimicry are Adelpha butterflies, which are agile insects and show remarkable colour pattern convergence. We tested the ability of naive b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 73 publications
2
27
0
Order By: Relevance
“…Thirdly, there is evasive behaviour where an animal signals that its future flight from the predator will be too fast or agile for the predator to capture it (Páez et al . 2021); this is often a morphological signal that is invariant across individuals. If we include this wider ambit of aposematic‐like signals, we immediately recognize that there are actually many examples of aposematism in birds that have hitherto been overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, there is evasive behaviour where an animal signals that its future flight from the predator will be too fast or agile for the predator to capture it (Páez et al . 2021); this is often a morphological signal that is invariant across individuals. If we include this wider ambit of aposematic‐like signals, we immediately recognize that there are actually many examples of aposematism in birds that have hitherto been overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…While sonar jamming is a likely function of this high‐density acoustic trait, it is also possible that X . praedicta's sounds act as a salient cue for different effect, such as warning predators of low capturability (i.e., evasive aposematism (Páez et al, 2021)). Alternatively, although palatability studies with hawkmoths have so far revealed a lack of chemical defense in the adult form (Kawahara & Barber, 2015), X .…”
Section: Resultsmentioning
confidence: 99%
“…The sphingine file and scraper strategy in general seems to produce similar effects across species, as X. praedicta and the two other representative genera (Figure 2; Barber & Kawahara, 2013) demonstrate some of the highest duty cycle, longest duration, and lowest dominant frequency sounds among described bat-responding moths (Figure 2). While sonar jamming is a likely function of this highdensity acoustic trait, it is also possible that X. praedicta's sounds act as a salient cue for different effect, such as warning predators of low capturability (i.e., evasive aposematism (Páez et al, 2021)).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“… Maan and Cummings, 2012) or ease of capture (e.g. Páez et al, 2021) may also vary according to the movement of the signaller. Species-level comparisons across several different taxonomic groups reveal differences in colour patterns according to mobility: among lizards, species with striped colour patterns are more mobile than those with cryptic patterns ( Halperin et al, 2017 ); small, fast-moving snakes that hunt actively tend to have longitudinal stripes, while large, slow snakes that ambush hunt have blotched patterns ( Allen et al, 2013 ); longitudinal bands occur more frequently on the eye-lines of faster moving, slender fish species, and vertical bands occurred more frequently on sharply turning, deep-bodied fishes ( Barlow, 1972 ).…”
Section: Motion and Colour Pattern Designmentioning
confidence: 99%